2010
DOI: 10.1007/s00248-010-9787-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Is a Stronger Determinant than Sex of the Mouse Gut Microbiota

Abstract: The mammalian gut microbiota is considered to be determined mostly by diet, while the effect of genotype is still controversial. Here, we examined the effect of genotype on the gut microbiota in normal populations, exhibiting only natural polymorphisms, and evaluated this effect in comparison to the effect of sex. DNA fingerprinting approaches were used to profile the gut microbiota of eight different recombinant inbred mouse lines of the collaborative cross consortium, whose level of genetic diversity mimics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
152
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 40 publications
14
152
1
3
Order By: Relevance
“…Moreover, expression of a human caspase conferred differential susceptibility to Listeria monocytogenes infection in male and female transgenic mice, apparently due to estrogen interactions (Yeretssian et al, 2009). However, Kovacs et al (2011) found no gender differences in the CC mice of their study. As is the case with maternal lineage, undetected genetic or epigenetic factors that were not adequately controlled could manifest in sexbased differences between strains.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Moreover, expression of a human caspase conferred differential susceptibility to Listeria monocytogenes infection in male and female transgenic mice, apparently due to estrogen interactions (Yeretssian et al, 2009). However, Kovacs et al (2011) found no gender differences in the CC mice of their study. As is the case with maternal lineage, undetected genetic or epigenetic factors that were not adequately controlled could manifest in sexbased differences between strains.…”
Section: Discussionmentioning
confidence: 68%
“…However, siblings of other strains were markedly dissimilar in microbial flora. Recently, DNA fingerprinting techniques revealed no maternal-derived differences in gut bacteria of CC mice (Kovacs et al, 2011). However, Ley et al (2005) found lineage influences to extend to more than one generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, microbial assemblages may in part be hereditary, as host genotype may influence susceptibility to colonization by certain microbes (Bonder et al., 2016; Kovacs et al., 2011; van Opstal & Bordenstein, 2015; Turpin et al., 2016). However, it remains unclear to which extent host relatedness contributes to microbiota similarity in wildlife, especially in relation to the factors discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show that within-and among-population differences in gut microbiota reflect host genetic diversity, even after accounting for differential colonization. We use these findings to infer that metacommunity structure of the stickleback microbiota is more strongly driven by host genotype (likely reflecting species filtering processes (Ley et al, 2008;Benson et al, 2010;Kovacs et al, 2011)) than by colonization.…”
Section: Introductionmentioning
confidence: 99%